2015
DOI: 10.1002/jsfa.7084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fermentation concentrate of Hericium caput‐medusae (Bull.:Fr.) Pers. on growth performance, digestibility, and intestinal microbiology and morphology in broiler chickens

Abstract: Dietary supplementation with HFC increased gut Lactobacilli and Bifidobacteria counts and inhibited E. coli growth, improved nutrient utilisation and intestine villus structure, and thus improved the growth of broilers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Sample excreta collections were pooled within a cage and sub-sampled following the method of total excreta collection by Sakomura & Rostagno (2007). The Cr 2 O 3 content was determined by the method described by Shang et al (2016). The DM and EE were analysed according to the procedures of the Association of Official Analytical Chemists (AOAC 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample excreta collections were pooled within a cage and sub-sampled following the method of total excreta collection by Sakomura & Rostagno (2007). The Cr 2 O 3 content was determined by the method described by Shang et al (2016). The DM and EE were analysed according to the procedures of the Association of Official Analytical Chemists (AOAC 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen was determined using an FP-528 nitrogen determinator (LECO Corporation, USA). The apparent nutrient retention (ANR) was calculated using this formula, based on quantity of feed and faeces nutrients with appropriate corrections for differences in DM content (Shang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results, it was concluded that the ethanolic extract of Albizia procera has significant in-vivo antioxidant activity 53 and can be used to protect tissue from oxidative stress [54][55][56][57] .…”
Section: Other Productsmentioning
confidence: 99%
“…Mushrooms are very attractive in food and pharmaceutical researches due to their bioactive components, such as phenolic compounds, terpenes, steroids and polysaccharides, that have a variety of biological activities. [6,7,8]. The mushroom's compounds possess antifungal activity [9], antigenotoxic [10], antioxidant [5],antiproliferative [11], anticancer [12], antihyperlipidemic [13], antihypertensive, anti-nociceptive and immunostimulanting [14], hypocholesterolemic, antiatherogenic [15], and stress reducing properties [16].…”
Section: Introductionmentioning
confidence: 99%